A case of lymphomatoid papulosis arising on the upper lip. Issue 4 (July 2021) - Narahara, Shun; Mitate, Eiji; Murayama, Naoya; Kuwatsuka, Yutaka; Murota, Hiroyuki; Nagano, Kenichi; Katase, Naoki; Fujita, Shuichi; Asahina, Izumi
Abstract: Lymphomatoid papulosis (LyP) is one of primary cutaneous CD30-positive large T-cell lymphoproliferative disorders (CD30 + PCLPD) that seldom arises in the oral region. We report here an extremely rare case of LyP arising on the lip. A 25-year-old female developed a painless mass on her right upper lip, which gradually grew and became painful. She visited her dermatologist who diagnosed it as herpes labialis and administered valacyclovir, but the lesion was unchanged. Then, she was referred to our department. At first visit, the mass was elastic, slightly hard, scarlet in color, and 15 mm in diameter. As T-cell lymphoma was initially diagnosed following incisional biopsy, we referred her to the Departments of Hematology and also Dermatology at our hospital. Bone marrow examination showed no neoplastic changes, and positron emission tomography-computed tomography revealed no other lesion except on the lip. Although new lesions appeared on her upper lip during the examinations, the lesions spontaneously disappeared without further treatment after the biopsy. The final diagnosis was CD30 + PCLPD pathologically and LyP clinically. No recurrence was found during the 10-month follow-up period.